ISLAM DAN ILMU PENGETAHUAN: MENGHADIRKAN TEOLOGI DIALEKTIS MENGHADAPI MASA DEPAN AGAMA DAN MANUSIA - Akromullah, Hamdan (JURNAL AL-AQIDAH, 2021)
This article looks at how the early development of Islamic theology loaded with political nuances is such that dialectically gave rise to many theological schools. On the other hand the development of the idea that value-free science has brought about the bankruptcy of science itself. So much so that in the next development science demands moral values in its development. This is what experts suspect that the 21st century is the century of religion. Where it is expected at that time the active role of religion can determine the next human development. The approach used is historical philosophical, which describes how the development of Islamic theological thought then analyzes and elaborates it with the objective conditions of recent science in search of solutions. In conclusion, the dialogical relationship between the various branches of science is a hard urgent demand. Cataloging theology with social sciences such as anthropology, with a phenomenological approach. It is expected to create a paradigm of dialogical theological thought, which is an inclusive understanding. So that the difference of thought that exists is not used as an excuse as a trigger for external conflict let alone interen, as had happened in the middle of Islam. Even further it will be a solution to the problems that occur in the course of science specifically and the continuity of religion and human life.